Reliability analysis of an inter-story isolated structure under a main-aftershock sequence based on the Laplace asymptotic method - Yang, Fan; Li, Cheng; Wang, Taize; Liu, Dewen; Yao, Shunzhong; Li, Hui; He, Jiajun; Huo, Yiran; Lei, Min (Frontiers in Earth Science, 2023)
The actual ground motion is in the form of a sequence. After a strong mainshock, it is usually accompanied by multiple aftershocks. Technically, the damage of the structure under multiple earthquakes is more serious than that of the single earthquake. Most of the seismic studies are based on a single earthquake. To explore the influence of the main-aftershock sequence on the inter-story isolated structure. Herein, a three-dimensional finite element model of the inter-story isolated structure was established and the repeated method to construct the main-aftershock sequence was used. The Laplace asymptotic method of second-order second-moment was used to compare the reliability of the structure under the action of single mainshock and main-aftershock sequence under different seismic levels. The effects of the number of aftershocks, the location of isolation layer and the stiffness of isolation bearing on the structure were analyzed. The results show that aftershock would increase the failure probability of each substructure of the inter-story isolated structure, and the failure probability of the lower structure had the greatest influence, which was about 3.89 times that of the mainshock alone. The reliable probability of multiple and single aftershocks was similar, and the largest aftershock plays a major role. Aftershock also reduced the overall reliability probability of inter-story isolation structures. In the case of different isolation layer setting positions, the isolation layer was set at the top of the seventh story under the extremely rare earthquake level, which was reduced by about 6.01 %. Under the condition of different isolation bearing stiffness, the most decrease was about 7.88 % when the stiffness was 50 %.